1.
Resuelve los
a.
(3x + 4) (3x - 7)
b. (3x - 5y) (3x + 5y)
c.
(6 9 -3b) (2 a -6b)
d. (2x + 4) (5x + 8)
2. Resuelva (x + a),(x-a) y (x + a)
Respuestas
Respuesta dada por:
3
Respuesta:
Explicación paso a paso:
a. (3x + 4) (3x - 7)
=(3x+4)(3x+−7)
=(3x)(3x)+(3x)(−7)+(4)(3x)+(4)(−7)
=9x2−21x+12x−28
=9x2−9x−28
b. (3x - 5y) (3x + 5y)
=(3x+−5y)(3x+5y)
=(3x)(3x)+(3x)(5y)+(−5y)(3x)+(−5y)(5y)
=9x2+15xy−15xy−25y2
=9x2−25y2
c. (6 9 -3b) (2 a -6b)
=((6)(9)+−3b)(2a+−6b)
=(6)(9)(2a)+(6)(9)(−6b)+(−3b)(2a)+(−3b)(−6b)
=−6ab+18b2+108a−324b
d. (2x + 4) (5x + 8)
=(2x+4)(5x+8)
=(2x)(5x)+(2x)(8)+(4)(5x)+(4)(8)
=10x2+16x+20x+32
=10x2+36x+32
Este no entendi que es lo que necesitas igual lo intento cariño xd.
(x + a)
=a+x
(x-a)
=−a+x
Preguntas similares
hace 5 años
hace 5 años
hace 8 años
hace 8 años
hace 8 años
hace 9 años
hace 9 años